1998
DOI: 10.1128/aac.42.6.1417
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Sparfloxacin in the Serum and Vitreous Humor of Rabbits: Physicochemical Properties That Regulate Penetration of Quinolone Antimicrobials

Abstract: We have used a recently described animal model to characterize the ocular pharmacokinetics of sparfloxacin in vitreous humor of uninfected albino rabbits following systemic administration and direct intraocular injection. The relationships of lipophilicity, protein binding, and molecular weight to the penetration and elimination of sparfloxacin were compared to those of ciprofloxacin, fleroxacin, and ofloxacin. To determine whether elimination was active, elimination rates following direct injection with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…23,29 Higher lipophilicity has been shown to correlate with greater ocular penetration in several fluoroquinolones, including ciprofloxacin and ofloxacin. 30 In addition to greater penetration of the cornea and aqueous humor as shown by high C max and AUC 0-2 values, an optimal antibiotic agent would have higher potency-ie, lower MICs-and a wider spectrum of coverage against common ocular pathogens. Results of previously reported in vitro tests showed that gatifloxacin and moxifloxacin were more potent than the second-and third-generation fluoroquinolones, suggesting that these agents could provide advantages over the early-generation agents for treating and preventing ocular infections caused by Gram-positive organisms and atypical mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…23,29 Higher lipophilicity has been shown to correlate with greater ocular penetration in several fluoroquinolones, including ciprofloxacin and ofloxacin. 30 In addition to greater penetration of the cornea and aqueous humor as shown by high C max and AUC 0-2 values, an optimal antibiotic agent would have higher potency-ie, lower MICs-and a wider spectrum of coverage against common ocular pathogens. Results of previously reported in vitro tests showed that gatifloxacin and moxifloxacin were more potent than the second-and third-generation fluoroquinolones, suggesting that these agents could provide advantages over the early-generation agents for treating and preventing ocular infections caused by Gram-positive organisms and atypical mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic study was carried out by Miller (26) to correlate the physicochemical properties and drug elimination from vitreous following intravitreal injection. These authors had shown an excellent correlation between lipophilicity (Log D at pH 7.2) and vitreal elimination half-life following intravitreal injection in albino rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…(26) had previously reported a linear correlation between the lipophilicity (Log D at pH 7.2) and beta half-life using a small group (four) of structurally similar quinolones. How-…”
mentioning
confidence: 97%
“…As a result of the poor vascularization and the small diffusion surface, the ocular globe shows an abscess-like behaviour, with a very limited diffusion of antibiotics, especially those with a high protein binding rate and/or low liposolubility [20]. The main consequences of this fact are: (i) the drug concentration peak in vitreous humour is lower than the drug concentration peak in plasma, and (ii) the maximum drug concentration is reached with some hours of delay between plasma and vitreous humour.…”
Section: Blood-ocular Barriers [18]mentioning
confidence: 99%